2017
DOI: 10.1002/jobm.201700041
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in bacterial community in natural wetland‐river‐sea ecosystems

Abstract: Wetland-estuarine-marine environments are typical oxic/anoxic transition zones and have complex water flow-paths within the zone of mixing where freshwater interacts with ocean water. Little is known about the impact of this interaction on bacterial community structures or the relationship between bacterial community and geochemical factors in such transitional mixing environments. Hence, we investigated the distribution patterns and diversity in bacterial communities in the Yellow River estuary-coastal wetlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…Temporal and spatial variations in microbial biodiversity have been previously observed in natural wetlands [9,31,35] and constructed wetlands [4,14,30,32], but these studies have mostly emphasized soils [4,9,14,31,32], sediments [9,35] and rhizospheres [30]. The present study revealed the temporal and spatial dynamics of bacterial and archaeal richness, diversity and evenness in the water of an estuarine wetland.…”
Section: Distinct Seasonal Dynamics Of Planktonic Bacterial and Archasupporting
confidence: 52%
“…Temporal and spatial variations in microbial biodiversity have been previously observed in natural wetlands [9,31,35] and constructed wetlands [4,14,30,32], but these studies have mostly emphasized soils [4,9,14,31,32], sediments [9,35] and rhizospheres [30]. The present study revealed the temporal and spatial dynamics of bacterial and archaeal richness, diversity and evenness in the water of an estuarine wetland.…”
Section: Distinct Seasonal Dynamics Of Planktonic Bacterial and Archasupporting
confidence: 52%
“…4b). Primary examples included the genera Dechloromonas and Hydrogenophaga which are reported to be autohydrogenotrophic denitrifiers (Zhang et al, 2009b;Zhang et al, 2017b) and Geobacter which promotes the reduction of V(V) (Ortiz-Bernad et al, 2004). Enriched Nitrospira, Ideonella and Methyloversatilis took part in nitrogen cycling (Shi et al, 2017;Pepe-Ranney et al, 2015;Baytshtok et al, 2009).…”
Section: Microbial Communities and Mechanismsmentioning
confidence: 99%
“…It is also has the second largest sediment load flux to the ocean of any river (Poulton and Raiswell 2002;Pan et al 2013). Previous studies (Liu et al 2003;Qiao et al 2007;Gong et al 2015;Sheng et al 2015;Zhang et al 2017) have shown that the concentrations of ferrous iron (Fe(II)), ferric iron (Fe(III)), total iron (Fe), and ammonium (NH 4 + -N) were higher in the coastal marine sediment than in the Yellow River sediment, whereas the concentration of nitrate (NO 3 − -N) was higher in the riverine sediment than in coastal marine sediment. Patterns of IRB abundance and diversity can indicate their contribution to the biogeochemical cycles, while changes in community structures are associated with spatial variations in nutrients [i.e.,NO 3 − -N, NH 4 + -N, Fe(II), Fe(III)] in different habitats.…”
Section: Introductionmentioning
confidence: 95%
“…Salinity and pH in the overlying water at each site were measured with an electronic probe (Hydrolab MS5, HACH, USA). Nitrate (NO 3 − -N), ammonium (NH 4 + -N), total organic carbon (TOC) and total nitrogen (TN) in sediment samples, and the concentration of sulfate (SO 4 2− ) in the sediment pore waters were determined, as described in Zhang et al (2017). Dissolved ferrous iron (Fe(II)) was measured using a ferrozine-based assay (Lovley and Phillips 1987;Stookey 1970).…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation